Empathy and humanization in nursing is the key to holistic care: an ethical imperative in the comprehensive care of patients with HIV/AIDS - Cárdenas Vargas, Alfonso (2025)
Nursing care for people living with HIV has evolved significantly since the beginning of the epidemic, shifting from a biomedical approach to a person-centered paradigm. However, although biomedical and pharmacological advances have made HIV a chronic condition that is manageable, barriers related to stigma, discrimination, and dehumanized care still persist, undoubtedly affecting treatment adherence and quality of life. This essay critically analyzes the integration of empathy and humanization as imperatives and essential components of holistic nursing care for people with HIV. Through a reflection based on the available evidence, it problematizes the tension between the effectiveness of the technical dimension and the human dimension of care, questioning whether clinical competence without empathy is sufficient to achieve optimal health outcomes. It argues that empathy is not an optional attribute but a fundamental ethical requirement that directly influences adherence to highly active antiretroviral therapy (HAART), the reduction of internalized stigma, and mental health outcomes. Systemic barriers such as work overload and burnout syndrome are recognized, and finally, strategies are integrated to combine humanization and efficiency in the daily practice of holistic care.